Chryseobacterium tagetis sp. nov., a plant growth promoting bacterium with an antimicrobial activity isolated from the roots of medicinal plant (Tagetes patula) - Chhetri, Geeta; Kim, Inhyup; Kim, Jiyoun; So, Yoonseop; Seo, Taegun (Journal of antibiotics, 2022)
A novel plant growth-promoting and indole acetic acid (IAA) producing strain designated RG1 T was isolated from the roots of Tagetes patula (marigold) collected from Goyang, South Korea. The cells of strain RG1 T is aerobic, yellow, Gram-stain-negative, pleomorphic and non-motile. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain RG1 T belongs to the genus Chryseobacterium and is closely related to Chryseobacterium gwangjuense THG-A18 T (98.6%). The strain produced IAA (70.5 µg ml −1 ) in the presence of L -tryptophan and showed antimicrobial activity against Gram-negative bacterium Xanthomonas campestris pv. campestris KACC 10377 T . The isolate had a significant positive effect on rice plant shoot and root growth. The novel strain RG1 T had a draft genome size of 4,430,189 bp, with ten scaffolds and 3969 protein-coding genes. The digital DNA-DNA hybridization (dDDH) and average nucleotide identity (ANI) values between strain RG1 T and other closely related members ranged from 21.5 to 36.6% and from 79.2 to 86.6%, respectively. The genomic DNA G + C content was 34.8 mol%. Furthermore, anti-SMASH analysis of the whole genome revealed six putative biosynthetic gene clusters responsible for various secondary metabolites. The major respiratory quinone was MK-6 and the major fatty acids were iso-C 15:0 , summed feature 3 (comprising C 16: 1 ω 7 c and/or C 16: 1 ω 6 c ) and summed feature 9 (comprising iso-C 17: 1 ω 9 c and/or 10-methyl C 16:0 ). The major polar lipid is phosphatidylethanolamine. Based on the genotypic, chemotaxonomic and physiological data, strain RG1 T represents a novel species, for which the name Chryseobacterium tagetis sp. nov. is proposed. The type strain is designated as RG1 T ( = KCTC 82696 T = NBRC 115057 T ).